Subsurface Modeling Using Gravity Method for Geothermal Potential, Case Study: Mount Ciremai - Haq, Muhammad Syauqil; Haris, Abdul (CV. Green Publisher Indonesia, 2025)
Indonesia is located at three major tectonic plates which make Indonesia have mountain ranges, volcanic arcs, and fault zones, causing frequent seismic and volcanic activity. To understand how geological phenomena occur, subsurface analysis and modeling are required. This study aims to identify and map regional and residual gravity anomalies in the Mount Ciremai area using gravity survey methods. The analysis of these anomalies is utilized to interpret subsurface structures related to the geothermal system potential in the region. Gravity data used in this research were obtained from GGMplus satellite imagery, which were then processed to generate regional and residual anomaly maps. The gravity method was chosen for its ability to detect subsurface rock density variations, which are essential for revealing geological structures. This quantitative research uses an exploratory approach, aiming to identify major structural elements such as faults, magma chambers, and hydrothermal systems. Through gravity data processing and interpretation, the study also seeks to determine the main components of the geothermal system, including the heat source, reservoir, cap rock, and fluid pathways. The results are expected to contribute to a better understanding of subsurface geological characteristics and support geothermal energy exploration in the Mount Ciremai area.